Perceived HIV-risk and the preventive strategies: the case of the trafficked women of Edo state origin (2013)
This paper examines the peoples' perception of getting infected with HIV-AIDS and the preventive strategies known and adop'ed by trafficked and vulnerable Nigerian women of Edo State origin. The data were obtained from secondary sources which included literature searches and primary sources based on qualitative data obtained through structured interviews involving the trafficked and deported Edo ladies. A further source of the data was from a focused of group of vulnerable women in pdo State. The trafficking of young girls and the ignorance of HIV- status is a major factor for the spread of the HIV among sexually active people. The study reveals a high level of awareness, among the trafficked (deported): women and, a low level of awareness among the vulnerable women living in Edo State. There are high numbers of unprotected sexual practices with regular partners whose HIV statuses.are unknown and thus highly perceived HIV-risks among the most trafficked and a misconceived low perceived risks among the vulnerable. Te study concludes by recommending for the sensitization about the need to test for HlV-status and for the adoption of adequate behavioral change as key strategies for reducing HIV-risks.